Cyclodextrin-induced release of drug-entrapping liposomes associated with the solation of liposome gels. Issue 34 (10th August 2022) - Yamada, Hiromu; Yamana, Keita; Kawasaki, Riku; Yasuhara, Kazuma; Ikeda, Atsushi
Abstract : The solation of liposome gels owing to the addition of trimethyl-β-cyclodextrin (TMe-β-CDx) and the uptake of cationic liposomes released from liposome gels by Colon26 cells are demonstrated. Abstract : In this work, we demonstrate that liposome gels in which liposomes are connected by polyethylene glycol terminated by cholesterol groups at both ends can store hydrophilic and hydrophobic drugs in the gel interiors, inner aqueous phases, and lipid membranes. The addition of cyclodextrins (CDxs) as extrinsic stimuli led to the release of drug-entrapping liposomes due to the interactions between CDxs and cholesteryl groups and/or the alkyl chains of lipids. The addition of aqueous solutions of β-CDx, dimethyl-β-CDx, trimethyl-β-CDx, and γ-CDx (final concentration: 7.5 mM) induced the solation of liposome gels and the release of liposomes accompanying the solation. Furthermore, the addition of β-CDx led to the partial release of hydrophilic drugs encapsulated in the liposomes, although the drug release was scarcely observed in other CDxs. In particular, the addition of trimethyl-β-CDx, which has low cytotoxicity, accelerated solation, and cationic liposomes released from the gels were effectively taken up by murine colon cancer (Colon26) cells. Thus, we propose that liposomes released from liposome gels can function as drug carriers.